2008
DOI: 10.1007/bf03324742
|View full text |Cite
|
Sign up to set email alerts
|

Using the RT3 accelerometer to measure everyday activity in functionally impaired older people

Abstract: Walking can be distinguished from other activities by upper and lower cutoffs. The RT3 accelerometer should be used on the same side of the body. Different walking aids do not appear to affect RT3 counts in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Soundy et al developed treadmill-based cutoff values for the RT3 accelerometer based on the VM counts/ min (± SD) [15] and later used these values to discriminate activity levels in free living [38]. Sumukadas et al developed cutoff values based on the 95 percent CI for mean RT3 accelerometer VM counts/min in a series of laboratory-based level-ground walking and step-climbing activities [21]. These results provide support for the use of treadmill-based activity cutoff points within a nondisabled population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soundy et al developed treadmill-based cutoff values for the RT3 accelerometer based on the VM counts/ min (± SD) [15] and later used these values to discriminate activity levels in free living [38]. Sumukadas et al developed cutoff values based on the 95 percent CI for mean RT3 accelerometer VM counts/min in a series of laboratory-based level-ground walking and step-climbing activities [21]. These results provide support for the use of treadmill-based activity cutoff points within a nondisabled population.…”
Section: Discussionmentioning
confidence: 99%
“…Validation and reliability of the RT3 accelerometer for free-living research has been assessed under a number of laboratory-based conditions, including walking and running at standardized speeds on a treadmill [11,[14][15][16][17], using a shaker table [18][19], assessing various mobility tasks [3], and performing structured activities [20]. A recent study has also demonstrated the ability of the RT3 accelerometer to discriminate between a series of standardized laboratory-based activities [21]; however, the ability of RT3 accelerometer vector magnitude (VM) counts to discriminate specific activities in free living has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…11 Physical activity levels were measured objectively using the RT3 Triaxial accelerometer (Stay Healthy Inc) during waking hours for 7 days. 7,12 Disease-specific quality of life was measured with the Minnesota Living With Heart Failure questionnaire. 13,14 The Functional Limitations Profile 15 a general health status tool, and the Hospital Anxiety and Depression scale 16 were also administered.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Minutes of walking were derived from accelerometry data by counting each minute of vector-summed activity between 250 cpm and 3000 cpm. We have previously shown that these thresholds accurately classify walking in older people using the RT3 accelerometer [18]. We did not attempt to classify activity as moderate, vigorous or other based on RT3 data given the uncertainty in RT3 count thresholds for these activities in an older population.…”
Section: Assessment Schedulementioning
confidence: 99%
“…The RT3 is a piezoelectric, triaxial accelerometer which has previously been validated in a number of different ways: it shows adequate test-retest reliability, it has been shown to discriminate walking from sedentary activity in older people, and it is responsive to interventions designed to increase physical activity [18][19][20]. Participants wore the accelerometer on the waistband anteriorly over the same hip during waking hours for a single 7-day period [20].…”
Section: Assessment Schedulementioning
confidence: 99%